Assessment of Commercially Available Immunoassays to Measure Glucocorticoid Metabolites in African Grey Parrot (Psittacus Erithacus) Droppings: A Ready Tool for Non-Invasive Monitoring of Stress - Cécile Bienboire-Frosini; Muriel Alnot-Perronin; Camille Chabaud; Pietro Asproni; Céline Lafont-Lecuelle; Alessandro Cozzi; Patrick Pageat (Animals, 2018)
Despite being undomesticated, African Grey Parrots (Psittacus erithacus) are commonly found in captivity, in zoos or as pets. Captivity can be an ongoing stressor. Non-invasive glucocorticoid metabolites (GCM) measurements from bird droppings are of interest for assessing stress but require careful evaluation in each newly studied species. This study describes the assessment of such methods for Psittacus erithacus to provide tools for evaluating stress and monitoring welfare. We evaluated 12 method combinations of GCM extraction and enzyme immunoassay (EIA) from a pool of African Grey Parrot droppings, through the validation of several analytical parameters. Then, Heterophil: Lymphocyte Ratios (HLR), another reliable stress marker, were determined and correlated to individual dropping GCM concentrations for 29 birds to determine whether the method is biologically relevant. We found that the best procedure to measure GCM in African Grey Parrot droppings is a combination of 60% methanol extraction measured using a Corticosterone EIA kit (Cayman Chemical Company) from fresh or dry droppings. The establishment of a significant correlation (Pearson coefficient correlation = 0.48; p = 0.0082) between HLR and GCM in the studied population confirmed the method biological relevance. This method can thus be applied to assess stress in Psittacus erithacus and support welfare monitoring in zoo populations.